Preliminary Trials with Tropical Conifers in Kerala State - Nair, P. N. (Indian Forester, 1971)
Results of trials so far carried out with tropical conifers in Kerala since 1965 indicate that a few species at least are suitable for introduction in this State. Of these, pines such as Pinus patula, P. insularis (P. kesia) and P. caribaea appear to be best suited for raising plantations at higher altitudes above 1200 m. Other species such as P. roxburghii, P. elliottii, P. pseudostrobus and P. oocarpa also come up fairly well in such altitudes. P. caribaea var. hondurensis, can come up fairly well in lower altitude and foot hill areas also. Among the other conifers Araucaria cunninghamii, Taxodium mucronatum and Cupressus lusitanica come up fairly well at higher altitudes above 800 m whereas Agathis robusta is more tolerant of altitude ranges extending down to 100 m. In general the higher altitude areas in Kerala above 1000 m with better distribution of rainfall appear to be good from a climatic point of view for selected tropical conifers such as P. patula, P. insularis, P. caribaea. P. oocarpa, Araucaria cunninghamii, Taxodium mucronatum and Agathis robusta.